The pharmacist in public health : education, applications, and opportunities - Truong, Hoai-An;Bresette, James L.;Sellers, Jill A. (Washington, D.C : American Pharmacists Association, 2010)
The Pharmacists in Public Health: Education, Applications, and Opportunities integrates public health concepts into pharmacy practice and empowers pharmacists and student pharmacists to become involved in public health.
Reviewing: Pharmacy in public health -- Integrating: Pharmacist's role in public health -- Developing: Public health pharmacists -- Educating and serving: Pharmacy in public health
Includes bibliographical references and index.
Keywords: PHARMACEUTICAL SERVICES -- UNITED STATES